تنفيذ التوجيه والإرشاد في حل مشكلات التعلم بالمدرسة الثانوية الحكومية فونوروكو - Imam, Rahma (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Guidance and counseling is one of the division in schools that helpstudents who are facing problems in school, including students' learningproblems. Learning difficulties is one of the most common issues amongstudents. This study aims to investigate the implementation of Guidanceand Counseling in overcoming learning difficulties. This research is aqualitative descriptive study, which used some data collection techniques:interview, observation and documentation. While the data analysistechnique used is descriptive analysis to describe the conditions ofGuidance and Counseling in MTs.N Ponorogo in overcoming learningdifficulties. Analysis of data used Miles and Huberman’s data analysis.The subjects were students of class VIII MTs.N Ponorogo, Guidance andCounseling Teachers, Principals, and Master of Class. The results of thisstudy indicate that factors that affect students' learning difficulties are twofactors, it is inside and outside factors. Inside factors such as health,interest to the subjects, intelligence, motivation and mood of student.While external factors include state of the school environment, familycircumstances, school environment, and technology. Implementation ofguidance and counseling to prevent students' learning difficulties areovercome difficulties in understanding himself; overcome difficulties inunderstanding environment that includes school environment, family andwider community; overcome difficulties in identifying and solvingproblems; overcome difficulties in performing their abilities, interests andtalents and guide them to choose the employment that appropriate.Preventing method of Guidance and Counseling in overcoming learningdifficulties including motivate students, directing and guiding students inovercoming learning difficulties, and explains the steps of learning.